Reducing dietary crude protein levels while meeting metabolizable protein requirements: Performance of dairy cows over a full lactation period - A. Lavery; A. Craig; A.W. Gordon; A. White; N. Barkley; C.P. Ferris (Journal of Dairy Science)
ABSTRACT: A total of 90 Holstein dairy cows (24 primiparous, 66 multiparous, mean parity = 3.0) were fed diets containing either 150, 160, or 170 g CP/kg DM from 8 to 180 DIM, with all diets designed to supply at least 100% MP requirements. On d 181, half of the cows in each treatment changed to a diet containing 140 g CP/kg DM (supplying 100% MP requirements), with the remaining cows continuing to be offered their original treatment diets. This resulted in 6 treatments in the mid-late lactation period (181–280 DIM): 150, 150/140, 160, 160/140, 170, and 170/140 g CP/kg DM. Decreasing dietary CP concentration from 170 to 150 g CP/kg DM did not affect DMI, milk yield, milk fat or protein yield in early lactation (8–181 DIM), but reduced MUN and the ratio of n-6 to n-3 fatty acids in milk, as well as serum albumin, globulin, total protein, and urea concentrations. In addition, reducing dietary CP content from 170 to 160 g CP/kg DM improved N use efficiency (NUE; milk N/N intake), with no further improvement with 150 g CP/kg DM. Treatment had no effect on apparent total-tract ration digestibility in early lactation. Urinary N output decreased with decreasing dietary CP content in early lactation, whereas manure N (fecal N plus urinary N) output increased. Urinary N/manure N decreased from 170 to 160 g CP/kg DM diet, whereas no further reduction was observed with the 150 g CP/kg DM diet. Cows that remained on the 150 g CP/kg DM treatment in mid-late lactation (181–280 DIM) had a lower DMI than those which remained on the diet containing 170 g CP/kg DM. Reducing the dietary CP concentration to 140 g CP/kg DM in mid-late lactation reduced DMI, milk yield, and milk fat and protein yields, compared with offering the 170 or 160 g CP/kg DM diet throughout lactation, possibly reflecting a response to oversupply of MP with the latter treatments, rather than an undersupply of MP with the former, although this is uncertain. Concentrations of C18:2 cis-9,trans-11 and the ratio of n-6 to n-3 fatty acids in milk were lower for cows offered diets containing 140 or 150 g CP/kg DM in mid-late lactation compared with 160 or 170 g CP/kg DM. Reducing dietary CP concentration from 170 to 140 g CP/kg DM improved NUE from 0.28 to 0.34 in mid-late lactation. Nitrogen digestibility was reduced when cows were offered the 140 g CP/kg DM diet compared with the 150 or 160 g CP/kg DM diet. Lowering the dietary CP concentration from 170 to 140 g CP/kg DM in mid-late lactation decreased N output in milk, feces, urine, and manure. These results indicate that a dietary CP content of 160 g CP/kg DM, which met the MP requirement of cows, may be optimal to support performance over a whole lactation, improve NUE, and reduce N excretion, thus contributing to a more sustainable approach to dairy cow production.